Flexible Devices: A Strategy to Modulate the Bending Coupled Microwave Magnetism in Nanoscale Epitaxial Lithium Ferrite for Flexible Spintronic Devices (Adv. Sci. 12/2018). Issue 12 (19th December 2018) - Shen, Lvkang; Lan, Guohua; Lu, Lu; Ma, Chunrui; Cao, Cuimei; Jiang, Changjun; Fu, Huarui; You, Caiyin; Lu, Xiaoli; Yang, Yaodong; Chen, Lang; Liu, Ming; et al.
Abstract : For flexible materials, knowledge of the bending coupled physical properties is very important for designing devices. In article number1800855, Ming Liu and co‐workers discuss a strategy to modulate the bending coupled microwave magnetism in epitaxial nanostructures. It is revealed that fabricating nanopillar arrays can be a good choice for flexible devices with stable properties under bending, while high‐quality film can be applied in tunable devices.